Effect of using flat hierarchical method on some aspects of muscular strength and straight serve skill for nascent tennis players - Anaam Abdul-ridha Dr. Suhad Qassim Dr. Abeer Dakhil (physical education and sport sciences college for women/ Baghdad University, 2020)
The researcher focused on the importance of the physical abilities of the tennis game, as this game is one of the games that are characterized by its specificity in performance as this game is characterized by continuous movement and dealing with different elements, so this game requires the development of muscle strength, which plays an important role in Performance skills in the game of tennis. There are several methods to develop strength, including flat hierarchical technique, which is one of the most common forms of training in the development of muscle strength.     As for the research problem, the researcher found a method that has an effect on the development of force. Therefore, the researcher tried to diversify and experiment in the training process through the use of a training method suitable for the youth category and taking into account their level. The researcher adopted a method for recognizing its effect on muscle strength and the skill of straight transmission in tennis as a modest contribution In order to improve the reality of this game and reach the players to the best levels. The study also aims to develop a training curriculum in a flat pyramid style and to identify the effect of flat hierarchical technique in some aspects of muscular strength and the skill of straight transmission of the nascent players in tennis. The researcher also hypothesized that there are statistically significant differences between the results of tribal and remote tests in some musculoskeletal aspects of tennis players There were statistically significant differences between the results of the tribal and remote tests in the skill of the straight transmission of the tennis players. As the researcher used the experimental method with one experimental group and the sample of the study consisted of (6) players emerging from tennis out of (10 players).     The study concluded with a set of conclusions and recommendations, the most important of which is that the flat hierarchical method has a positive effect on some aspects of muscular strength and the skill of straight transmission of the players who are born in tennis. The researcher also recommends the adoption of the training method on the flat hierarchical method in the development of force and the emphasis on the use of weight exercises in the training curriculum.